How digital infrastructure supports emerging forms of urban digital tourism in China - Jielong Huang; Wenbin Ling; Shanni Ye; Rabnawaz Khan; Qifu Lai (PLoS ONE, 2026)
China’s ongoing digital transformation, supported by proactive government policies, is fundamentally reshaping urban tourism through strategic development of digital infrastructure. This study employs a Difference-in-Differences (DID) model, taking the Broadband China policy as a quasi-natural experiment, to examine the driving effects and mechanisms of digital infrastructure development on emerging forms of urban digital tourism entrepreneurship. The results show that: (1) digital infrastructure development can facilitate the development of emerging forms for urban digital tourism entrepreneurship. Even after controlling for endogeneity, other policy intervention, and robustness in parallel trend testing, the outcome remains unchanged. Digital infrastructure has the potential to foster the growth of new types of urban digital tourism businesses by increasing the concentration of digital talent, the rate of technological innovation and application, and the level of government support. The driving effect is stronger in cities that have exceptional cultural value, well-allocated administrative resources, and excellent tourist resources. Coordination and information exchange in industrial chains are beneficial for nearby regions, but they pose a threat of marginalization to areas that aren’t immediately adjacent due to the impacts of resource siphoning. Therefore, the government should promote the transformation of urban tourism into intelligent and convenient, establish cross-city tourism alliances, and form a complementary mode of “technology and resources.” Simultaneously, it should make use of digital technology to accurately match the characteristics of the city and guide operators of the industry to efficiently make use of digital technology to identify market opportunities, integrate resources, and unleash the new kinetic energy of the industry’s development.